Clinical dietitian-led nutrition counseling and exercise to reduce cardiovascular risk in adults living with a BMI above 27 and severe mental illness: the NORMI-Heart trial protocol - Angelsen, Madeleine Elisabeth; Najar, Hemen; Svendsen, Mette; Thoresen, Magne; Peleikis, Dawn Elizabeth; Retterstøl, Kjetil (Frontiers in Nutrition, 2026)
BackgroundSevere mental illness (SMI) is associated with high cardiovascular disease (CVD) risk. Important contributors are poor diet quality, physical inactivity, and metabolic side effects of antipsychotic medication entailing significant weight gain. Evidence implies that dietary counseling delivered by clinical dietitians leads to greater improvements in diet quality, weight management, and cardiometabolic health than counseling delivered by non-specialist health personnel, especially when combined with increased physical activity. However, randomized controlled trials (RCTs) testing clinical dietitian-led nutrition counseling integrated with structured exercise across diverse treatment modalities in psychiatric care remain scarce.ObjectiveThe Norwegian Mental Illness Heart Health (NORMI-Heart) study will evaluate the efficacy and applicability of a 6-month lifestyle program, combining individualized, clinical dietitian-led nutrition counseling focused on weight reduction and improved dietary quality, and moderate-to-vigorous exercise training, on CVD risk in adults with SMI in Oslo, Norway.MethodsThis parallel-group RCT will recruit 70 overweight adults with SMI. Participants will be randomized to a 6-month diet and lifestyle intervention, or control. The intervention is individualized and includes monthly one-to-one sessions with a clinical dietitian focusing on heart-healthy eating and weight reduction, monthly supervised group exercise, and support to follow an individual exercise program. Control participants will receive treatment as usual (TAU). The NORMI-Heart Trial aims to evaluate the effect of the intervention on estimated CVD risk.Expected outcomesThis trial aims to provide evidence on the effectiveness, feasibility, and real-world applicability of clinical dietitian-led nutrition counseling combined with structured exercise for reducing CVD risk in individuals with SMI. Findings may strengthen the scientific and policy rationale for integrating clinical dietitians as a standard part of multidisciplinary mental health care. Results will also inform scalable, integrated lifestyle care models in mental health services.Trial registrationClinicalTrials.gov Identifier: [NCT07085923].